Study on the ability of black soldier fly larvae for reducing the house fly eggs in poultry manure - Hashim, Nor Haslina; Hamdan, Nurul Fatin Nabilah; Abdullah, Nor Maizzaty; Awang, Zarizi; Hamidon, Nuramidah (Penerbit UTHM, 2020)
Black soldier fly larvae (BSFL) are a good source of protein for aquaculture, animal feed, pet and human nutrition. Larvae have a healthy appetite and can be used to make household waste compost and residual agricultural. For previous study [1], observed that the BSFL can be grown in a variety of organic waste stream including pig manure, kitchen waste, fruits and vegetables, and given to the fish. In addition, the larvae benefit from the use of natural resources to overcome the problem of life cycle of widespread flies in the poultry farm openly. Therefore, it is important to note that the poultry farms release many particles into the air that endanger human health and the environment.